Are the Choice of Frame and Intraoperative Patient Positioning Associated With Radiologic and Clinical Outcomes in Long-instrumented Lumbar Fusion for Adult Spinal Deformity?. Issue 5 (14th May 2022) - Park, Hyung-Youl; Kim, Young-Hoon; Ha, Kee-Yong; Chang, Dong-Gune; Kim, Sang-ll; Park, Soo-Bin
Abstract: Background: Previous studies of patient positioning during spinal surgery evaluated intraoperative or immediate postoperative outcomes after short-instrumented lumbar fusion. However, patient positioning during long-instrumented fusion for an adult spinal deformity (ASD) might be associated with differences in intraoperative parameters such as blood loss and longer-term outcomes such as spine alignment, and comparing types of surgical tables in the context of these larger procedures and evaluating longer-term outcome scores seem important. Questions/purposes: (1) Do blood loss and the number of transfusions differ between patients who underwent multi-level spinal fusion with a Wilson frame and those with a four-poster frame? (2) Does restoration of lumbar lordosis and the sagittal vertical axis differ between patients who underwent surgery with the use of one frame or the other? (3) Do clinical outcomes as determined by Numeric Rating Scale and Oswestry Disability Index scores differ between the two groups of patients? (4) Are there differences in postoperative complications between the two groups? Methods: Among 651 patients undergoing thoracolumbar instrumented fusion between 2015 and 2018, 129 patients treated with more than four levels of initial fusion for an ASD were identified. A total of 48% (62 of 129) were eligible; 44% (57 of 129) were excluded because of a history of fusion, three-column osteotomy, or surgical indications other than degenerative deformity, and another 8% (10 of 129) were lost before the minimum 2-year follow-up period. Before January 2017, one surgeon in this study used only a Wilson frame; starting in January 2017, the same surgeon consistently used a four-poster frame. Forty patients had spinal fusion using the Wilson frame; 85% (34 of 40) of these had follow-up at least 2 years postoperatively (mean 44 ± 13 months). Thirty-two patients underwent surgery using the four-poster frame; 88% (28 of 32) of these were available for follow-up at least 2 years later (mean 34 ± 6 months). The groups did not differ in terms of age, gender, BMI, type of deformity, or number of fused levels. Surgical parameters such as blood loss and the total amount of blood transfused were compared between the two groups. Estimated blood loss was measured by the amount of suction drainage and the amount of blood that soaked gauze. The decision to transfuse blood was based on intraoperative hemoglobin values, a protocol that was applied equally to both groups. Radiologic outcomes including sagittal parameters and clinical outcomes such as the Numerical Rating Scale score for back pain (range 0-10; minimal clinically important difference [MCID] 2.9) and leg pain (range 0-10; MCID 2.9) as well as the Oswestry Disability Index score (range 0-100; MCID 15.4) were also assessed through a longitudinally maintained database by two spine surgeons who participated in this study. Repeated-measures analysis of variance was used to compare selected radiologic outcomes between the two groups over time. Results: Blood loss and the total amount of transfused blood were greater in the Wilson frame group than in the four-poster frame group (2019 ± 1213 mL versus 1171 ± 875 mL; mean difference 848 [95% CI 297 to 1399]; p = 0.003 for blood loss; 1706 ± 1003 mL versus 911 ± 651 mL; mean difference 795 [95% CI 353 to 1237]; p = 0.001 for transfusion). Lumbar lordosis and the sagittal vertical axis were less restored in the Wilson frame group than in the four-poster frame group (7° ± 10° versus 18° ± 14°; mean difference -11° [95% -17° to -5°]; p < 0.001 for lumbar lordosis; -22 ± 31 mm versus -43 ± 27 mm; mean difference 21 [95% CI 5 to 36]; p = 0.009 for the sagittal vertical axis). Such differences persisted at 2 years of follow-up. The proportion of patients with the desired correction was also greater in the four-poster frame group than in the Wilson frame group immediately postoperatively and at 2 years of follow-up (50% versus 21%, respectively; odds ratio 3.9 [95% CI 1.3 to 11.7]; p = 0.02; 43% versus 12%, respectively; odds ratio 5.6 [95% CI 1.6 to 20.3]; p = 0.005). We found no clinically important differences in postoperative patient-reported outcomes including Numeric Rating Scale and Oswestry Disability Index scores, and there were no differences in postoperative complications at 2 years of follow-up. Conclusion: The ideal patient position during surgery for an ASD should decrease intra-abdominal pressure and induce lordosis as the abdomen hangs freely and hip flexion is decreased. The four-poster frame appears advantageous for long-segment fusions for spinal deformities. Future studies are needed to extend our analyses to different types of spinal deformities and validate radiologic and clinical outcomes with follow-up for more than 2 years. Level of Evidence Level: III, therapeutic study.